POLA KOMUNIKASI KELOMPOK INFORMASI MASYARAKAT (KIM) PRIGEN PASURUAN DALAM PENYEBARAN INFORMASI KE MASYARAKAT - Herdono, Ismojo; Mutqiyyah, Rizqi (Universitas Muhammadiyah Jember, 2019)
The existence of the community information group (Kelompok Informasi Masyarakat/ KIM) plays the strategic role in establishing the human resources. Furthermore, this community holds its capacity as both the social community and non-formal organization, oftentimes doing a direct interaction with the people. This scrutiny is to analyze the patterns of communication run by the community information group in Lumbangrejo, Jatiarjo and Tretes villages, which are parts of the Prigen sub-district, Pasuruan Regency, East Java.This qualitative research is set out through a descriptive case study method, which is through investigating the real-life contexts phenomena, by taking advantage of various resources. The type of this study is a descriptive, that only describes or shows the cases in more depth. The outcome of this probe is to reveal the communication patterns of the community information group above in undertaking its role as the disseminators of information, technology, and innovation to the public.The conclusion of this analysis figures that patterns of communication applied in the community information group of Prigen Subdistrict, Pasuruan Regency, are the combinations amid interpersonal communication, utilization of technology and two ways communication. Nonetheless, as the part of opinion leaders, this community yet needs to strengthen its human resources in the form of transformation of both expertise and automation, whether it is supported by the government, universities, and NGOs. Thus, performance can be significantly optimal.